Utilization of Non-Composted Human Hair Hydrolysate as a Natural and Nutrient-Rich Liquid Fertilizer for Sustainable Agro-Applications and Bio-Waste Management - Yetilmezsoy, Kaan; Ilhan, Fatih; Kiyan, Emel (MDPI, 2025)
Human hair, commonly considered a discarded organic waste, is a keratin-rich material with remarkable potential for sustainable agriculture as an innovative resource. This study systematically explored the potential of non-composted human hair hydrolysates as eco-friendly and nutrient-rich liquid fertilizers, emphasizing their ability to enhance agricultural sustainability and mitigate organic waste accumulation. Eight distinct hydrolysates prepared with alkaline solutions were evaluated for their effects on plant growth using red-hot chili pepper (Capsicum frutescens) as the primary model under greenhouse conditions. The present study introduces a novel approach by employing an advanced digital image analysis technique to quantitatively assess 37 distinct plant growth parameters, providing an unprecedented depth of understanding regarding the impact of liquid human hair hydrolysates on plant development. Additionally, the integration of pilot-scale field trials and multi-species evaluations highlights the broader applicability and scalability of these hydrolysates as sustainable fertilizers. Collectively, these features establish this research as a pioneering contribution to sustainable agriculture and bio-waste management. The top-performing hydrolysates (KCaMgN, KMgN, KCaN) demonstrated significant enhancements in plant growth metrics, with fresh weight reaching up to 3210 mg, projected leaf area of approximately 132 cm2, and crown diameter of 20.91 cm for the best-performing formulations, outperforming a commercial organomineral fertilizer by 20-46% in overall growth performance. Furthermore, observational studies on various species (such as bird of paradise flower (Strelitzia reginae), avocado (Persea americana), lemon (Citrus limon L.), Mazafati date (Phoenix dactylifera L.), and red mini conical hot pepper (Capsicum annuum var. conoides) and field trials on long sweet green peppers (Capsicum annuum) confirmed the broad applicability of these hydrolysates. Toxicity assessments using shortfin molly fish (Poecilia sphenops) validated the environmental safety of plants cultivated with hydrolysates. These findings highlight that human hair hydrolysates offer a sustainable alternative to synthetic fertilizers, contributing to waste management efforts while enhancing agricultural productivity.
Keywords: bio-waste management; eco-friendly fertilizer; human hair hydrolysate; plant growth metrics; sustainable agriculture; GROWTH; SEEDLINGS; Science & Technology - Other Topics; Environmental Sciences & Ecology